Global economic trends and social development - Ajit Singh (United Nations Research Institute for Social Development (UNRISD), 2000)
This paper reviews the policy debate on development issues and examines the economic prospects for developing countries at the beginning of the twenty-first century. It is specifically concerned with the question of whether developing countries will be able to meet the employment and poverty reduction goals set by the World Summit for Social Development, held in Copenhagen in 1995. What policies at the national and international level will be most helpful in this respect? The introductory part of the paper notes that the Social Summit coincided with one of the worst financial crises up to that time in developing economies-Mexico's 'Tequila Crisis' in 1994 and 1995. It is suggested that, notwithstanding that crisis, the immediate economic prospects for developing countries in 1995 appeared much brighter than they do today in the wake of recent economic and financial crises in Asia, Latin America and Russia. The paper notes that, in contrast to the uneven economic performance of the economies of developing countries in the period since the Social Summit, the policy debate has in many ways taken a definite step forward. The main part of the paper provides a systematic investigation of the factors that determine whether or not developing countries will be able to eradicate poverty and achieve full employment with rising productivity and real wages. The paper looks specifically at the following aspects. First, it considers the economic record of developing countries and policy issues raised by this analysis. Second, it examines the complex interrelationships between economic growth, unemployment, poverty reduction and income inequality, both conceptually and empirically. This analysis gives attention to the notion of full employment, the relationship between technical change and unemployment, the economic significance of the information and communications technology revolution, and labour market theories of unemployment and inflation. Third, the paper looks at the changed historical conjuncture for economic development and for the development policy debate. The following themes and related analytical and policy questions are emphasized: Liberalization and globalization-Contrary to theoretical expectations, why has the actual experience of many developing countries with liberalization and globalization been negative rather than positive, i.e. why has it often resulted in crises rather than faster growth? Also, are these failures simply a matter of incorrect policies, or are there more fundamental flaws from the perspective of developing countries, with respect to the institutional arrangements of the world economy under liberalization and globalization? Washington Consensus-Has the Washington Consensus failed? What lessons should be learned from the implementation of that policy programme? Asian financial and economic crisis-A very important and influential thesis concerning the Asian crisis suggests that the failure of Asian countries during 1997-1999 can be ascribed mainly to the dirigiste and corporatist model of capitalism that many of these countries were following. The paper examines this thesis critically. A central policy implication of these analyses is that developing countries need to attain a trend increase in their growth rates, possibly to their pre-1980 long-term rates of about 6 per cent per year. This would enable them to achieve and maintain meaningful 'full employment' in the spirit of the Social Summit, with rising real wages and increasing standards of living. Although faster growth will help to reduce poverty, the latter is affected by other important variables as well-notably inflation, inequality of income and asset distribution, instability of economic growth and government fiscal policies. Women, in particular, are adversely affected by macro-economic instability. In the absence of adequate social security systems, the burden of women's paid as well as unpaid work increases during economic downturns. What is required, therefore, to meet the employment and poverty reduction goals of the Social Summit is not only fast growth, but also better quality growth. The last part of the paper highlights the shortcomings of the present institutional arrangement of liberalization and globalization. It indicates why and how these arrangements make it difficult for developing countries to achieve high rates of economic growth. Indeed, it is suggested that this regime is sub-optimal for both developing and developed countries. It is argued that, today, the main constraints on faster long-term economic growth in both developing and developed countries do not lie on the supply side but on the demand side. In principle, the world has the technological and intellectual capacity, as well as the human and material resources, to achieve the fast growth required to fulfil the aims of the Social Summit. The paper suggests that such growth will, however, only be realized in practice if the alternative strategy outlined is adopted. This involves the pursuit of faster growth of real world demand through co-ordinated expansion by industrialized countries and the introduction of special and differential treatment for developing countries in a number of key spheres. In brief, an essential argument of this paper is that, instead of the present organization of the world economy, a global Keynesian regime of managed world trade and controlled global capital movements is more likely to benefit both developed and developing countries. Together with genuine international co-operation as well as more harmonious relations between employers, employees and governments nationally, this would deliver both fast growth and high quality growth. Such growth would help bring full employment and rising wages in both groups of countries. In analytical terms, the paper stresses the significance of co-ordination failures on the demand side as the main obstacles to economic progress, rather than supply-side deficiencies. In order for the rate of growth of real world demand to be compatible with production possibilities on the supply side, new institutions are required to resolve the co-ordination problems on a sustained, long-term basis.
Keywords: 330